Sequencing and titrating approach of therapy in heart failure with reduced ejection fraction following the 2021 European Society of Cardiology guidelines: an international cardiology survey. (23rd November 2022) - Fauvel, Charles; Bonnet, Guillaume; Mullens, Wilfried; Giraldo, Clara Ines Saldarriaga; Mežnar, Anja Zupan; Barasa, Anders; Tokmakova, Mariya; Shchendrygina, Anastasia; Costa, Francisco Moscoso; Mapelli, Massimo; Zemrak, Filip; Tops, Laurens F.; et al.
Abstract: Aims: In symptomatic patients with heart failure and reduced ejection fraction (HFrEF), recent international guidelines recommend initiating four major therapeutic classes rather than sequential initiation. It remains unclear how this change in guidelines is perceived by practicing cardiologists versus heart failure (HF) specialists. Methods and results: An independent academic web‐based survey was designed by a group of HF specialists and posted by email and through various social networks to a broad community of cardiologists worldwide 1 year after the publication of the latest European HF guidelines. Overall, 615 cardiologists (38 [32–47] years old, 63% male) completed the survey, of which 58% were working in a university hospital and 26% were HF specialists. The threshold to define HFrEF was ≤40% for 61% of the physicians. Preferred drug prescription for the sequential approach was angiotensin‐converting enzyme inhibitors or angiotensin receptor–neprilysin inhibitors first (74%), beta‐blockers second (55%), mineralocorticoid receptor antagonists third (52%), and sodium–glucose cotransporter 2 inhibitors (53%) fourth. Eighty‐four percent of participants felt that starting all four classes was feasible within the initial hospitalization, and 58% felt that titration is less important than introducing a new class. Age, status in training, and specialization in HF field were the principal characteristics that significantly impacted the answers. Conclusion: In a broad international cardiology community, the 'historical approach' to HFrEF therapies remains the preferred sequencing approach. However, accelerated introduction and uptitration are also major treatment goals. Strategy trials in treatment guidance are needed to further change practices. Abstract : The latest European guidelines for heart failure with reduced ejection fraction (HFrEF) patients recommend initiating four major therapeutic classes rather than the sequential initiation from the previous guidelines. Without any evidence from randomized controlled trials, the perception and the practical approach to these guidelines by practicing cardiologists remain unclear. We found that left ventricular ejection fraction (LVEF) ≤40% remains the most frequent threshold to define HFrEF and the 'historical' approach to HFrEF drug titration remains the most popular sequencing approach. However, most participants felt that starting all four classes was feasible within the initial hospitalization and that titration is less important than introducing a new class. This is the first and largest survey providing real‐world data on HFrEF drug introduction and titration after the latest European heart failure guidelines. Even if the 'historical' sequencing approach remains dominant, starting all four classes in a short‐time period was perceived as feasible. Strategy trials in treatment guidance are now needed to demonstrate the safety and define the best treatment implementation approach. ACEi, angiotensin‐converting enzyme inhibitor; ARNi, angiotensin receptor–neprilysin inhibitor; BB, beta‐blocker; MRA, mineralocorticoid receptor antagonist; SGLT2i, sodium–glucose cotransporter 2 inhibitor.